PENINGKATAN MINAT BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA MELALUI STRATEGI PEMBELAJARAN AKTIF TIPE TIPE INDEX CARD MATCH DI KELAS VI SDN 24 BARUNG-BARUNG BELANTI - Erlisman Erlisman (JURNAL MANAJEMEN PENDIDIKAN, 2018)
ABSTRACTLearning interest is one of the factors that are important for student success in learning. However, the learning interest of the sixth grade students of SDN 24 Barung-Barung Belanti in mathematics was found to be still low. The purpose of this study was to describe and obtain information about increasing student learning interest in mathematics subjects through Active Learning Strategy Type of Index Card Match Type in Class VI SDN 24 Barung-Barung Belanti Ujung Gading. This research is a classroom action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. Research data was collected using a test sheet. Data is analyzed using percentages. Based on the results of the research and discussion that has been stated, it can be concluded that the Active Learning Strategy Type Index Card Match Type can increase students' learning interest in mathematics in Class VI SDN 24 Barung-Barung Belanti. Student learning interest in cycle I was 69.67, increasing to 84.36.Keywords: Learning Interest, Mathematics Learning, Active Learning Strategy Type Index Card Match Type